Early Buddhist transmission and trade networks mobility and exchange within and beyond the northwestern borderlands of South Asia - Neelis, Jason Emmanuel. (Dynamics in the History of Religions, 2011)
This exploration of early paths for Buddhist transmission within and beyond South Asia retraces the footsteps of monks, merchants, and other agents of cross-cultural exchange. A reassessment of literary, epigraphic, and archaeological sources reveals hisorical contexts for the growth of the Buddhist saṅgha from approximately the 5th century BCE to the end of the first millennium CE. Patterns of dynamic Buddhist mobility were closely linked to transregional trade networks extending to the northwestern borderlands and joined to Central Asian silk routes by capillary routes through transit zones in the upper Indus and Tarim Basin. By examining material conditions for Buddhist establishments at nodes along these routes, this book challenges models of gradual diffusion and develops alternative explanations for successful Buddhist movement.